If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + 12q = 16 Solving 40 + 12q = 16 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 12q = 16 + -40 Combine like terms: 40 + -40 = 0 0 + 12q = 16 + -40 12q = 16 + -40 Combine like terms: 16 + -40 = -24 12q = -24 Divide each side by '12'. q = -2 Simplifying q = -2
| 8x+4=-20 | | 15y-18=3(3y-5) | | 5x-7+2x=3x-2+4x | | 49-6x=3x+23 | | x^2+4x-195=0 | | x^2+20x-48=0 | | -2-(-1)= | | 3x+5=-2x+1 | | 8-8x=60-22x | | 71-3x=2x+6 | | -24f^2-r^2=0 | | (2x^2+8x+3)+(x^2+2)= | | 5x+1=2x-8 | | x^2+16x-11=0 | | 1.75t^2-4t=0 | | -15*3= | | (-9)(4)(1)= | | -x-7=x-1 | | a-9=-16 | | x/2+2x/3+x/4-x/6=10 | | -x^2-7x-12=0 | | x-7.9=-6.7 | | 6x-16=50 | | 6+-8+5= | | 25x=21x+24x+4 | | -8+3h=2(h-5) | | x-5+4x+2=2x-7 | | -4m+4(m+2)=2-6m | | 11-7x=127-35x | | x-279= | | 5x^2-12x+2=0 | | 6-14*4= |